Student Affairs Professionals’ Perspectives on Leading Student Development in the 21st Century University: An Inquiry Driven Exploration - Holmes, Barbara; Parker, DeJuanna; Holmes, Courtney (Advances in Social Sciences Research Journal, 2023)
As higher education prepares to respond to post-pandemic university student challenges, the role of student affairs professionals becomes more critical. Student affairs professionals undergird the student experience from admission to graduation and must be prepared to address the new needs of enrolled students. The researchers used paticipatory action research methods to collect and analyze narrative data. The following themes emerged from the study: 1) The Value of Professional Development , 2) Importance of Inter-departmental Relationships, 3) Relevance of Shared Vision and Goals, 4) Enhancement of the Student Experience through Impassioned Action, and 5) Leadership Growth through Informed Reflection.